Foreign aid and sustainable energy - Luis Gomez-Echeverri (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Energy is linked to most of the major global challenges of the twenty-first century. Poverty eradication, climate change, ecosystem management, world health and security are all influenced by energy, its availability, cost, emissions and other impacts. Unfortunately, energy systems as currently configured are not contributing effectively to the realization of most goals agreed upon by the international community. In order for energy systems to help deliver on the promises of these goals (e.g., stabilizing greenhouse gases emissions at levels agreed upon by the United Nations Framework Convention on Climate Change, helping countries achieve universal energy access by 2030 and better energy security) they would need to be significantly transformed. Because this transformation will need to be pursued in a global and cooperative basis, foreign aid must necessarily play a major role in this effort. This paper surveys some of the challenges of foreign aid to the energy sector in a rapidly changing environment, and the changes that it has had to make to be relevant and effective. The purpose of this paper is to undertake a brief examination of the energy foreign aid landscape within this changing context in order to extract lessons learned and determine best practices.
Keywords: A0; F0; O0; Q0; 330; sustainable energy; energy systems transformation; foreign aid; international cooperation